2020
DOI: 10.3389/fimmu.2020.576897
|View full text |Cite
|
Sign up to set email alerts
|

CD10+ Cells and IgM in Pathogen Response in Lumpfish (Cyclopterus lumpus) Eye Tissues

Abstract: Lumpfish (Cyclopterus lumpus), a North Atlantic “cleaner“ fish, is utilized to biocontrol salmon louse (Lepeophtheirus salmonis) in Atlantic salmon (Salmo salar) farms. Lumpfish require excellent vision to scan for and eat louse on salmon skin. The lumpfish eye immune response to infectious diseases has not been explored. We examined the ocular response to a natural parasite infection in wild lumpfish and to an experimental bacterial infection in cultured lumpfish. Cysts associated with natural myxozoan infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…6C,D). The anti-lumpfish-IgM IgY antibody we previously used on lumpfish tissues stained spotted wolffish head kidney in a pattern consistent with that observed in lumpfish head kidney 6 (Supplemental Fig. 6G,H) and strongly stained leukocytic cells in the choroid body/rete mirabile with a pattern similar to Sox9 expression in this tissue (Supplemental Figs.…”
Section: Detection Of Chondrogenesis and Immune Markers In Ocular Tis...supporting
confidence: 72%
See 3 more Smart Citations
“…6C,D). The anti-lumpfish-IgM IgY antibody we previously used on lumpfish tissues stained spotted wolffish head kidney in a pattern consistent with that observed in lumpfish head kidney 6 (Supplemental Fig. 6G,H) and strongly stained leukocytic cells in the choroid body/rete mirabile with a pattern similar to Sox9 expression in this tissue (Supplemental Figs.…”
Section: Detection Of Chondrogenesis and Immune Markers In Ocular Tis...supporting
confidence: 72%
“…Our work nonetheless provides a basis to further explore the visual system of spotted wolffish, which are designated a threatened species in Canada. In previous work, we characterized the visual system of the North Atlantic lumpfish [1][2][3][4][5][6][7] . The work herein on spotted wolffish suggests some differences (scleral cartilage thickness, shape and reactivity) and similarities (expression of cellular and immune markers PCNA, IgM and CD45), between the two species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL1R2 participates in the negative regulation of IL-1 via competitive inhibition (Cardoso et al, 2020;Zhou et al, 2019). Studies have confirmed that CD40-related pathways are important for resistance against a variety of parasites (Gendron et al, 2020;Subauste, 2009).…”
Section: Transcriptome Analysis Of Immune-and Energy-related Genesmentioning
confidence: 95%